2022
DOI: 10.1002/oby.23389
|View full text |Cite
|
Sign up to set email alerts
|

The microsomal triglyceride transfer protein inhibitor lomitapide improves vascular function in mice with obesity

Abstract: Objective In this study, the effect of lomitapide, a microsomal triglyceride transfer protein inhibitor, on the cardiovascular function in obesity was investigated. Methods Eight‐week‐old C57BL/6 mice were fed with high‐fat diet for 12 weeks in the presence and absence of lomitapide. Lomitapide was administered by gavage (1 mg/kg/d) during the last 2 weeks of high‐fat feeding. Body weight, blood glucose, body composition, and lipid profile were determined. Vascular function and endothelial function markers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Xie et al also found that Mtp iKO mice fed a high-fat-fructose-cholesterol diet for 10 weeks exhibited a sustained reduction in hepatic TG ( Xie et al, 2021 ). MTP inhibitor lomitapide, has also shown beneficial effects in improving obesity, blood glucose, lipids, and blood vessels ( Hooper et al, 2015 ; Munkhsaikhan et al, 2022 ). Lomitapide, however, targets both intestinal and hepatic MTP.…”
Section: Effects Of the Genes Involved In Regulating Dietary Triglyce...mentioning
confidence: 99%
“…Xie et al also found that Mtp iKO mice fed a high-fat-fructose-cholesterol diet for 10 weeks exhibited a sustained reduction in hepatic TG ( Xie et al, 2021 ). MTP inhibitor lomitapide, has also shown beneficial effects in improving obesity, blood glucose, lipids, and blood vessels ( Hooper et al, 2015 ; Munkhsaikhan et al, 2022 ). Lomitapide, however, targets both intestinal and hepatic MTP.…”
Section: Effects Of the Genes Involved In Regulating Dietary Triglyce...mentioning
confidence: 99%